1958
DOI: 10.6028/jres.060.052
|View full text |Cite
|
Sign up to set email alerts
|

Stress-strain relationships in yarns subjected to rapid impact loading: 5. Wave propagation in long textile yarns impacted transversely

Abstract: T he behavior of an infi nitely long flexib le fil a men t after transverse impact is treated theoret.icall y. The fil a ment is ass u med to have a tension-strain curve that is always co ncave dow nward, and to have no short-ti me creep or stress-rei fixation effects. Under most cond itions the impact in itiates a varia bl e strain t hat prop agates down the fil a ment between an "elasLic wave" fro nt a nd a " plastic wave" front. A tra nsverse wave, shaped li ke an inverLed V, then travels in t he co nstan t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0

Year Published

1964
1964
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(116 citation statements)
references
References 5 publications
5
111
0
Order By: Relevance
“…The gauge length of a single yarn is related to the contact time between the bullet and each layer (i.e. the product of longitudinal wave velocity and contact time equals the gauge length 15,16 ), and its maximum value will be the distance between the shot location and the edge of the panel (shot-to-edge distance). Figure 14 shows pullout marks at the edges of a frontal layer (circled area), which supports the assumption that the 1 st layer and all the following layers have the same gauge length that is equal to the shot-to-edge distance in this case.…”
Section: Analysis Of Energy Dissipation From the Experimentalmentioning
confidence: 99%
“…The gauge length of a single yarn is related to the contact time between the bullet and each layer (i.e. the product of longitudinal wave velocity and contact time equals the gauge length 15,16 ), and its maximum value will be the distance between the shot location and the edge of the panel (shot-to-edge distance). Figure 14 shows pullout marks at the edges of a frontal layer (circled area), which supports the assumption that the 1 st layer and all the following layers have the same gauge length that is equal to the shot-to-edge distance in this case.…”
Section: Analysis Of Energy Dissipation From the Experimentalmentioning
confidence: 99%
“…According to Smith et al [10] when the projectile is in contact with the yarn, ahead of the elastic wave front the strain is zero, and behind it, the strain is constant and can be calculated from:…”
Section: Absorbed Energiesmentioning
confidence: 99%
“…Many parameters affect on ballistic performance of hybrid composite targets such as materials, structures of composite, dimensions, boundary conditions and etc [7,8,9]. Smith et al [10] studied the behaviour of an infinite long yarn under transverse impact. They showed that the impact creates longitudinal and transversal waves on a single yarn which propagate down the yarn.…”
mentioning
confidence: 99%
“…By considering the average velocity in the contact zone of the deformation cone, the inertial force F 2i that acts on the projectile during the formation and movement of the deformation cone is obtained by (16) The tensile force that acts on the projectile F 2L is the transverse component of the tensile stresses in the unsheared fiber layers (17) where h 2 is the total thickness of the unsheared fiber layers, h 2 =h t -h 1 and is the dynamic tensile strength of the laminate. Thus, total force can be obtained by (18) The relation between and the strain of yarns based on the Smith et al [31] …”
Section: Ceramic Equationmentioning
confidence: 99%